Pengawasan dan evaluasi program bahasa arab di Pondok Pesantren Hafsah Binti Umar, Batu, Jawa Timur - Hafizatur Rahmi; Bisri Mustofa; Faisol; Athira Fakhriatuz Zamanai (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This paper is entitled Supervision and Evaluation of the Arabic Language Program. The method used by the author in preparing this paper is descriptive, analysis of description and analysis has the same meaning, namely describing, this method is done by describing or describing the data, while the method used is library research method (library research), library research is a study used to collect information and data with the help of various materials in the library such as documents, books, magazines, journals, historical stories, etc. The results of this study indicate that the one who evaluates the program carried out at the boarding school is the chairman of the foundation, asking each teacher who teaches in their respective fields, especially Arabic teachers if it is related to the type of evaluator, this cottage is classified as an internal evaluator because officers or program implementing members who are evaluated, namely the chairman of the foundation. Based on the evaluation program carried out by the chairman of the foundation, it can be seen that the chairman of the foundation evaluates it by asking every program that has been implemented by each teacher in their respective fields at the end of each semester. According to Stefanus Supriyanto and Nyoman Anita Damayanti (2006) in general, evaluation can be divided into two types, namely formative evaluation, and summative evaluation.